Fast Numerical Simulation of Symmetric Flat Rolling Processes for Inhomogeneous Materials Using a Layer Model − Part I: Basic Theory. Issue 8 (6th June 2016) - Schmidtchen, Matthias; Kawalla, Rudolf
Abstract : In the first part, a brief introduction to a general non‐isothermal layer model for symmetric but inhomogeneous rolling conditions is presented. The model is based on an extended slab theory. Additional to conventional approaches, a phenomenological layer thickness model for NS‐layers and its application to several rolling conditions is briefly described in part I. Within the course of computation for the stress and strain state internal stresses at the entrance and exit of the roll gap are predicted as a closing condition for the derived set of kinematic and kinetic equations. They transform elastically outside the roll gap to residual stresses. In this part, first comparisons are given to finite element solutions and experimental investigations. The results of an extensive case study will be given in part II. Due to the used coupling between kinematics and kinetics, a significant improvement of the slab theory in relation to a local description of an inhomogeneous plane strain deformation and stress state is found. Abstract : A general non‐isothermal layer model for symmetric but inhomogeneous rolling conditions is presented. It is based on an extended slab theory with an additional layer thickness model for NS‐layers of arbitrary mechanical properties. Internal stresses at the entrance and exit of the roll gap are predicted as a closing condition for the derived set of kinematic and kinetic equations.